JUMPA Vol. 4 No. 1, Feb 2017 PENGARUH CURRENT RATIO, NET PROFIT MARGIN DAN TOTAL ASSETS TURN OVER TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014: PENGARUH CURRENT RATIO, NET PROFIT MARGIN DAN TOTAL ASSETS TURN OVER TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Arfianto Cahyadi Sekolah Tinggi Ilmu Ekonomi YAI; Ali Munar Sekolah Tinggi Ilmu Ekonomi YAI (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2017)
In this script that has been investigated is the influence of Current Ratio, Net Profit Margin and Total Assets Turn Over to Dividen Payout Ratio on consumption goodsmanufacturing companies listed in Indonesia Stock Exchange. In this research there are four variables, that is Current Ratio (CR) as the independent variable (X1), Net Profit Margin (NPM) as the independent variable (X2), Total Assets Turn Over (TATO) as the independent variable (X3) and Dividen Payout Ratio (DPR) as the dependent variable (Y). The method used is quantitative research methods. The purpose of this research was to determine the factors that influence the Dividen Payout Ratio. In this research using observational data n = 45 on the consumption goods manufacturing companies listed on the Indonesia Stock Exchange. The results of the analysis CR to DPR there is positive influence and no significant from thitung( 1,091 ) < ttabel ( 2,017 ). The results of the analysis NPM to DPR are positive influence and significant of thitung ( 5,853 ) > ttabel ( 2,017 ). The results of the analysis TATO to DPR there is positive influence and no significant of thitung ( 1,988 ) > ttabel (2,017). There is a simultaneous effect of CR, NPM and TATO of the DPR has significant influence that the views of the value of Fhitung was 11,897 bigger than the value Ftabel 2,833.